Ergonomics of an In‐Patient Hospitalization - Amy Louise Gilliland (Health Expectations)
ABSTRACT This article documents inpatient work, including activities, number of nurses, shift changes and other staff encounters for the first time. In 2022, the researcher (patient) had a traumatic limb injury and began three 6–8 day stays in three different hospitals. Nursing care was provided by 37 different nurses and 23 certified nursing assistants in 50 different shifts over 21 days. There were 35 other unique encounters by other medical care staff. As an experienced qualitative researcher, the patient relied on field observation skills. Thirty‐eight distinct inpatient activities were grouped into five general categories: Logistics, Arrangements, Self‐care, Healing and Social Management. This article reveals that patients inside the hospital actively engage in various tasks to navigate and manage their health‐related goals. These responsibilities may be overwhelming for the patient, who is without resources to solve their own problems. Patient Contribution This paper is 100% from the patient's perspective and their original contribution.